EFFECTIVENESS OF A FAMILY-BASED CARE MANAGEMENT MODEL FOR STROKE CAREGIVERS: A RANDOMIZED CONTROLLED TRIAL. (11th November 2018) - Lou, V; Tang, J; Lum, T; Lau, G; Fong, K; Cheng, C; Fu, J
Abstract: Background and Objective: Every year, around 22, 000 people who suffer from stroke discharge to home or institutional care in Hong Kong. Existing evidence-based services targeting stroke patients are mostly patient-oriented. Family-oriented intervention is under-developed. Stroke causes profound impacts not only on the patient but also on the whole family. It often disrupts existing family dynamics, affecting almost each of the family member. We initiated "WeRISE: Stroke Family Empowerment Project" to test a family-oriented care management intervention on its effectiveness to reduce caregiver burden and enhance family functioning. Methodology: A standardized protocol on case referral procedure, inclusion and exclusion criteria for case recruitment, and five care management intervention sessions were developed and executed. A randomized controlled trial was piloted with 95 families within a twelve months of period, including 48 families in experimental group and 47 in control group. Standardized assessments including patients ADLs, IADLs and mobility status, and caregivers' burden, perceived support, and family functioning at recruitment, immediately and 2 months after intervention were measured. Findings: As compared to control group participants, experimental group participants recorded significant increase on perceived support and reduced caregiving burden. Conclusion: Family-oriented care management is found to be effective in supporting families who are taking care of stroke survivors. Service implications were discussed.